2004
DOI: 10.1128/aem.70.12.7481-7486.2004
|View full text |Cite
|
Sign up to set email alerts
|

Viable but Nonculturable Vibrio cholerae O1 in the Aquatic Environment of Argentina

Abstract: In Argentina, as in other countries of Latin America, cholera has occurred in an epidemic pattern. Vibrio cholerae O1 is native to the aquatic environment, and it occurs in both culturable and viable but nonculturable (VNC) forms, the latter during interepidemic periods. This is the first report of the presence of VNC V. cholerae O1 in the estuarine and marine waters of the Río de la Plata and the Argentine shelf of the Atlantic Ocean, respectively. Employing immunofluorescence and PCR methods, we were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 30 publications
2
62
0
3
Order By: Relevance
“…The hypothesis that cholera epidemics are triggered by environmental factors has been embraced by many environmental microbiologists, climatologists, and ecologists during the last decade (18)(19)(20). The fact that cholera epidemics seem to occur in several different foci simultaneously (21, 22) is often cited as evidence for an environmental component to its epidemiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that cholera epidemics are triggered by environmental factors has been embraced by many environmental microbiologists, climatologists, and ecologists during the last decade (18)(19)(20). The fact that cholera epidemics seem to occur in several different foci simultaneously (21, 22) is often cited as evidence for an environmental component to its epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the nonculturable state by definition is a condition when cells are incapable of forming a colony on commonly used media, it has been impossible to isolate the strains responsible for generating such cells in the environment. Thus, reported demonstrations of the existence of viable but nonculturable (VBNC) V. cholerae cells in the environment relied on fluorescent antibody techniques (19,20). Some reports suggest that V. cholerae can be converted to a VBNC state under defined laboratory conditions, and in one such case, nonculturable cells were putatively converted to viable cells by passage through the guts of human subjects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, V. cholerae O1 was frequently detected in estuary and coastal waters, and growth in sterile-filtered natural seawater under defined laboratory conditions has been reported (Binsztein et al, 2004;Louis et al, 2003;Mourino-Perez et al, 2003;Worden et al, 2006). In addition, laboratory studies using artificial seawater demonstrated growth of V. cholerae O1 down to a salinity of 5 g l 21 (Singleton et al, 1982a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Their purity was checked by taking the ratio of their absorbance at A260/A280 nm. The yield of each sample was also calculated by using the following formula: A260 × dilution factor × 50 µg ml -1 PCR amplification reaction for detecting VCO1/ VCO139 genes of V. cholera Amplification reaction was carried out for V. cholerae O1 and O139 strains associated with bloom/scum materials using above DNA preparations and primer pairs specific for VCO1 and VCO139 genes as detailed subsequently (Binsztein et al, 2004), procured from Imperial Life Sciences, India. Reaction mixture was prepared according to Jungblut and Neilan (2006) and Kumar et al (2011) and thermal cycling was performed according to the Binsztein et al (2004) with an initial denaturation step at 94°C for 5 min, followed …”
Section: Dna Extraction From Bloom/scummentioning
confidence: 99%
“…Reaction mixture was prepared according to Jungblut and Neilan (2006) and Kumar et al (2011). Thermal cycling and subsequent electrophoresis of amplified products was carried out according to the Binsztein et al (2004) using the primer pairs selective for VCO1 and VCO139 genes.…”
Section: Extraction Of Dna From Colonies Of V Choleraementioning
confidence: 99%